Effects Of Chitosan And Whey Powder Supplementation On Mineral Metabolism And Digestive Enzyme Activity In Broiler Chicks: Evidence Synthesis And A Methodological Framework (Texas Journal of Agriculture and Biological Sciences, 2026)
Improving feed efficiency while reducing reliance on antibiotic growth promoters remains a key challenge in modern broiler production. This paper synthesizes international and CIS literature on chitosan (a cationic biopolymer) and whey powder (a dairy by-product rich in high‑biological‑value proteins and bioactive peptides), focusing on two mechanistic endpoints: mineral metabolism (Ca, P, Mg) and digestive enzyme activity (amylase, lipase, protease). Using a scoping‑review approach, studies published between 2010 and 2026 were mapped across PubMed, Cambridge Core, MDPI, Google Scholar, and open regional databases. Data were extracted on dosage, duration, measurement protocols, and key zootechnical outcomes. The synthesis indicates that chitosan may modulate intestinal barrier integrity, microbiota balance, and mineral bioavailability through adsorption and ion‑exchange properties, whereas whey powder may support metabolic stability via high‑quality protein fractions and peptides, with downstream effects on gut morphology and nutrient utilization. Local studies from Uzbekistan report beneficial shifts in growth performance, mineral indicators, and bone‑related metrics when chitosan and whey are applied in combination. The paper proposes an evidence matrix, a conceptual mechanism model, and practical methodological recommendations for future controlled trials.